GAMBARAN HASIL UJI SARING HEPATITIS B PADA PENDONOR DARAH DI UNIT TRANSFUSI DARAH RSUD RADEN MATTAHER PROVINSI JAMBI - Witi Karwiti; Sholeha Rezekiyah; Wuni Sri Lestari; Eka Fitriana; Fardiah Tilawati S.; Nasrazuhdy Nasrazuhdy; Budiyanto Budiyanto (Journal of Indonesian Medical Laboratory and Science, 2022)
Hepatitis B occurs in people throughout the world and is one of the world's major health problems. Hepatitis B virus infection can develop into chronic hepatitis, liver cirrhosis, liver cancer and even death. This disease is caused by the hepatitis B virus which is transmitted through exposure to blood, and does not cause specific symptoms so that an infected person can carry out blood donor activities. Blood donors are people who donate blood or components to patients for the purpose of healing diseases and restoring health. Donor blood needs to be screened for screening tests to avoid the risk of disease transmission through blood screening tests for infectious infections through blood transfusion (IMLTD). One of them is a screening test for hepatitis B to detect Hepatitis B surface antigens (HBsAg). Research method: This research is descriptive. The purpose of the study: to find out the description of the results of hepatitis B strain test on blood donors based on the type of donation in the Blood Transfusion Unit of Raden Mattaher Hospital Jambi Province in 2019. Data analysis using bivariate and univariate. Results: 335 blood donors were 6 (1.8%) people with reactive HBsAg results. Conclusion: Based on the type of donation from 83 voluntary donors, there were 2 (2.4%) reactive HBsAg people, while 252 donor replacements were found in 4 (1.6%) reactive HBsAg people. Suggestion: Donors with reactive test results should be notified, so counseling can be done and referred to a confirmation check.